2014
DOI: 10.1037/a0035869
|View full text |Cite
|
Sign up to set email alerts
|

What accounts for the rapid detection of threat? Evidence for an advantage in perceptual and behavioral responding from eye movements.

Abstract: Countless studies have reported that adults detect a variety of threatening stimuli more quickly than positive or neutral stimuli. Despite speculation about what factors drive this bias in detection, very few studies have examined the exact search strategies adults use to detect threatening stimuli in visual search. The current research uses an eye-tracker in a classic visual search paradigm in attempt to elucidate the factors that lead to rapid threat detection. Our results replicate previous work, demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 52 publications
3
38
0
Order By: Relevance
“…There are some additional factors that researchers should consider when using the paradigm. First, researchers should think carefully about the experimental set-up, as labeling the targets, the participant's emotional state, and the participant's emotional traits (e.g., phobias, anxiety) have all been shown to affect the results 1,11,[15][16] . Further, researchers should take caution in choosing appropriate target stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some additional factors that researchers should consider when using the paradigm. First, researchers should think carefully about the experimental set-up, as labeling the targets, the participant's emotional state, and the participant's emotional traits (e.g., phobias, anxiety) have all been shown to affect the results 1,11,[15][16] . Further, researchers should take caution in choosing appropriate target stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is worth noting that head-mounted or desk-mounted eye-tracking technology can be used in combination with the touch-screen visual detection paradigm to capture exact fixations as participants search for target stimuli. Eye-tracking produces more than just latency to touch the screen-it also produces data on latency to first fixate the target, total fixations and fixation time to each distracter before first fixating the target, and latency from the first fixation to making a behavioral response 11 . By differentiating between these measures, researchers can disambiguate the potential mechanisms that drive rapid detection.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…This could echo the subcortical pathway involving the pulvinar, the amygdala, and the striatum, which may lead to a coarse but fast visual information processing 40, 41. Indeed, because of its evolutionary relevance, this preserved route may induce a preattentive and autonomic bias toward threatening stimuli like angry faces 42, 43. However, experimental data failed to fully support this “angry faces advantage” (whereby angry faces are detected more quickly than others).…”
Section: Facial Emotion Recognition In Pdmentioning
confidence: 99%
“…A number of previous studies on emotional modulation of eye-movement behavior found evidence for faster detection of emotional stimuli (e.g., Bannerman, Milders, de Gelder, & Sahraie, 2009;Bannerman, Milders, & Sahraiem, 2009;Kissler & Keil, 2008;LoBue, Matthews, Harvey, & Stark, 2014). For example, Bannerman, Milders, de Gelder, & showed a decrease in saccade latency when a saccade is directed to the location of a threatening stimulus relative to a nonthreatening stimulus.…”
mentioning
confidence: 98%
“…However, similar to the covert attention studies discussed before, most eye movement studies presented emotional stimuli that were always to some extent task relevant. For example, observers were instructed to saccade toward or away from the emotional stimulus (e.g., Bannerman, Milders, de Gelder, & Sahraie, 2009;Kissler & Keil, 2008;Nummenmaa, Hyönä, & Calvo, 2006) or to assess the valence, category or memory of presented pictures (Calvo & Lang, 2004;Humphrey et al, 2012;Lang et al, 1993;LoBue et al, 2014). Therefore, observers had to process and attend to the emotional stimulus in order to perform the task.…”
mentioning
confidence: 99%